2006
DOI: 10.1007/s00167-006-0105-y
|View full text |Cite
|
Sign up to set email alerts
|

Tibial press-fit fixation of the hamstring tendons for ACL-reconstruction

Abstract: Press-fit fixation of patellar tendon bone anterior cruciate ligament autografts is an interesting technique because no hardware is necessary to achieve fixation. Up till the present point, there is no biomechanical data available for the tibial press-fit fixation of the hamstring tendons. Hamstring tendons of 21 human cadavers (age: 41.9 +/- 13.1 years) were used. A press-fit fixation with looped semitendinosus and gracilis tendons secured by a tape (T) over a bone bridge, or by a baseball-stitched suture (S)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…Our results for the interference screw fixation show maximum failure loads comparable to the results of other studies [10,14,24]. The load-to-failure of the pull-press suture showed a significantly higher result than a conventional baseball-stitched suture and the interference screw fixation.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results for the interference screw fixation show maximum failure loads comparable to the results of other studies [10,14,24]. The load-to-failure of the pull-press suture showed a significantly higher result than a conventional baseball-stitched suture and the interference screw fixation.…”
Section: Discussionsupporting
confidence: 91%
“…Comparable studies using a 1 mm oversized interference screw [24] showed a higher stiffness than found in our setup [10]. The stiffness of the pull-press group showed results that came close to the results of oversized interference screws (162 ± 27 N/mm Sysorb; Centerpulse Medical AG, Winterthur, Switzerland and 115 ± 34 N/ mm for Smart Screw ACL [10,14]).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Yet, the stability results are excellent. Some surgeons, in particular Dargel et al [18] and Jagodzinski et al [19], used a press-fit technique with no fixation and have achieved good results.…”
Section: Introductionmentioning
confidence: 98%